Local Economic Development Based on Regional Potential as a Means of Increasing Community Participation in Tanjung Laut Indah (JED (Jurnal Etika Demokrasi), 2025)
This study investigates community participation in local economic development in Tanjung Laut Indah Village, Bontang City, East Kalimantan, emphasizing the role of regional potential in fostering inclusive and sustainable development. Using a qualitative approach guided by the Sustainable Livelihood Framework, the research explores how residents engage in economic activities across sectors such as fisheries, micro-enterprises, and technology-based initiatives, while identifying factors that enable or hinder participation. Findings indicate heterogeneous participation patterns, with approximately 45% of residents actively engaged, 30% participating passively, 15% not involved, and 10% displaying counterproductive behavior, reflecting variations in motivation, capacity, and social perspectives. Active participants, including fishermen, housewives, and youth with technological skills, demonstrate the capacity for grassroots-driven initiatives to generate economic value, strengthen social cohesion, and sustain development programs, whereas passive or resistant groups highlight challenges associated with top-down approaches and misaligned incentives. Key barriers to participation include limited skills, resource constraints, social and institutional obstacles, and conflicting interests, which vary across age, gender, and time, necessitating targeted and context-sensitive strategies. The study emphasizes the importance of multidimensional, evidence-based interventions that combine capacity-building, inclusive decision-making, equitable resource allocation, and recognition of diverse contributions to enhance participation. By illustrating how local potential can serve as a foundation for participatory development, this research contributes to both theory and practice, providing insights for policymakers and development practitioners to design effective, equitable, and resilient local economic initiatives that promote sustainable growth, social equity, and community empowerment.